Bank-Lending Standards, the Cost Channel and Inflation Dynamics - Sylvia Kaufmann; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2009)
If firms borrow working capital to finance production, then nominal interest rates have a direct influence on inflation dynamics, which appears to be the case empirically. However, interest rates may only partly mirror the cost of working capital. In this paper we explore the role of bank lending standards as a potential additional cost source and evaluate their empirical importance in explaining inflation dynamics in the US and in the euro area.
Keywords: E40; E50; 330; New Keynesian Phillips Curve; Cost Channel; Bank Lending Standards; Bayesian Analysis; New-Keynesian Phillips Curve; Kreditgeschäft; Bankenpolitik; Inflation; Bayes-Statistik; Kointegration; Schätzung; USA; EU-Staaten